Analysis of services sector of the Republic of Serbia during COVID-19 pandemic - Đurković-Marić Tijana; Vukmirović Goran; Marić Radenko (Ekonomija: teorija i praksa, 2023)
The aim of this paper is to analyze the situation in the services sector after the global pandemic caused by the virus corona, as well as an overview of the disruptions caused by the pandemic in the global and national market. The service sector suffered the greatest consequences of the pandemic and the initial lockdown. All services, except trade and retail, have discontinued their business activities. The research will cover comparisons of the situation in the services sector in the period before, during and after the global pandemic. Based on the results from the global market and the situation in the services sector of certain countries in the recovery period, a forecast of the situation in the domestic market will be made. The research will focus specifically on tourism, hospitality and retail as the sectors which were the most affected by the pandemic in the Republic of Serbia market, accounting for almost 20% of national GDP. The results of the survey will indicate to the relevant institutions, economic policy makers and management of the service companies what measures must be taken to return the level of income and profitability to the period before the pandemic. Suggestions and guidelines for future research are outlined in the paper.